(3GdTaGA aj GdefWbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPG cJGH GdTaG ddTjN GdQFjS CHj Ydi GdMSjf YHO Gddg Hf SjfG hHYO abO cGfJ eMHJi ddYdhe GdMcejI hQZHJi ai EbJHGS GdeYGQa GdMcejI hCeG GdQjGVjGJ abO cGf YedgG Ydi SHjd GdGNJUGQ ai SGda GdReGf s
(3BNQgG (B:s
(3jfJgi CKfGA GdebGdI GdQGHYI ai Gdaf GdSGOS ai GdLOdjGJ ai ehGVY GdNGUI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1055s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdadSaI hGdefWbs